Vitronectin‐activated αvβ3 and αvβ5 integrin signalling specifies haematopoietic fate in human pluripotent stem cells. (3rd March 2021) - Shen, Jun; Zhu, Yaoyao; Zhang, Shuo; Lyu, Shuzhen; Lyu, Cuicui; Feng, Zicen; Hoyle, Dixie L.; Wang, Zack Z.; Cheng, Tao
Abstract: Objectives: Vitronectin (VTN) has been widely used for the maintenance and expansion of human pluripotent stem cells (hPSCs) as feeder‐free conditions. However, the effect of VTN on hPSC differentiation remains unclear. Here, we investigated the role of VTN in early haematopoietic development of hPSCs. Materials and Methods: A chemically defined monolayer system was applied to study the role of different matrix or basement membrane proteins in haematopoietic development of hPSCs. The role of integrin signalling in VTN‐mediated haematopoietic differentiation was investigated by integrin antagonists. Finally, small interfering RNA was used to knock down integrin gene expression in differentiated cells. Results: We found that the haematopoietic differentiation of hPSCs on VTN was far more efficient than that on Matrigel that is also often used for hPSC culture. VTN promoted the fate determination of endothelial‐haematopoietic lineage during mesoderm development to generate haemogenic endothelium (HE). Moreover, we demonstrated that the signals through αvβ3 and αvβ5 integrins were required for VTN‐promoted haematopoietic differentiation. Blocking αvβ3 and αvβ5 integrins by the integrin antagonists impaired the development of HE, but not endothelial‐to‐haematopoietic transition (EHT). Finally, both αvβ3 and αvβ5 were confirmed acting synergistically for early haematopoietic differentiation by knockdown the expression of αv, β3 or β5. Conclusion: The established VTN‐based monolayer system of haematopoietic differentiation of hPSCs presents a valuable platform for further investigating niche signals involved in human haematopoietic development. Abstract : Compared with Matrigel (MTG), vitronectin (VTN) was required for the mesoderm to acquire higher endothelial‐hematopoietic potential. The promoting effect of VTN on early hematopoiesis was dependent on αvβ3 and αvβ5 integrins. Inhibition of αvβ3 and αvβ5 impaired HE development without affecting EHT.